Public Sphere and Education in the Light of Social Representation Theories - Marta Krasuska-Betiuk (University of Lower Silesia, 2015)
The text is an attempt to show the relationship between the public sphere and education through the prism of the main assumptions of Serge Moscovici's social representation theory (SRT). With this end in view, the beginning briefly presents Habermas's understanding of the public sphere and then invokes by S. Jovchelovitch's thesis about the existence of a dialectical relationship between the public sphere and social representations. The end raises questions about the social representations of empirical research in the field of education, with several examples and conclusions of international studies, for which the theory of social representations was the main theoretical and methodological perspective.